Myocarditis associated with immune checkpoint inhibitors: Practical considerations in diagnosis and management - Muhammet Gürdoğan; Kenan Yalta (Anatolian Journal of Cardiology, 2020)
Immune checkpoint inhibitors (ICI) have caused radical changes in the treatment scheme of many types of cancer in the past 10 years. ICIs are specific monoclonal antibodies that increase T-cell mediated immune response against cancer cells. Despite important advances in cancer treatment, uncontrolled activation of cytotoxic T cells has brought along many autoimmune clinical side effects, especially acute myocarditis. Although the incidence of ICI-related myocarditis is about 1%, it is remarkable in terms of mortality rate reaching 46% and demonstrating the necessity of rapid diagnosis and multidisciplinary approach. The present review aimed to summarize the heterogeneous symptomatology of ICI-associated myocarditis, clinical presentation ranging from elevated asymptomatic cardiac enzyme levels to cardiogenic shock, prominent diagnostic value of cardiac magnetic resonance imaging, and current information on the effectiveness of immunosuppressants in therapy.